Gombapyrones E and F, New alpha-Pyrone Polyenes Produced by Streptomyces sp. KMC-002 - Park, Hyun Bong; Yang, Hyun Ok; Lee, Kang Ro; Kwon, Hak Cheol (MDPI, 2011)
Microorganism-derived polyene polyketides have been shown to display a variety of biological activities and have attracted great interest due to their structurally intriguing chemical diversity. Two new polyenes were isolated from a culture broth of Streptomyces sp. KMC-002 obtained from a soil sample in an abandoned mine. The structures of these compounds were determined to be alpha-pyrone-containing polyene analogues through analyses of HRFABMS, UV and NMR data, and were named Gombapyrones E (1) and F (2). Gombapyrone E (1) showed antibacterial activity against Micrococcus luteus, Enterococcus hirae, Staphylococcus aureus and MRSA.
Keywords: ANTITUMOR-ANTIBIOTICS; MARINE ACTINOMYCETE; NATURAL-PRODUCTS; A-D; POLYKETIDE; METABOLITES; BIOSYNTHESIS; RESISTANCE; SPONGE